2013
DOI: 10.1556/oh.2013.29764
|View full text |Cite
|
Sign up to set email alerts
|

Acute cytomegalovirus infection-associated hemophagocytic syndrome in a patient treated with azathioprine

Abstract: The authors present the case of a 21-year-old woman with ulcerative colitis. Azathioprine treatment was complicated with pancytopenia and septic shock. Acute cytomegalovirus infection related to the immunosuppressive therapy, resulting in hemophagocytosis syndrome and neutropenic fever was diagnosed. Recovery was achieved by the administration of parenteral ganciclovir, broad spectrum antibiotic and complex intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Viral infection, which is often respiratory, is a common cause of secondary HLH and CMV‐associated HLH appear to be a particular risk in patients with ulcerative colitis treated with azathioprine [2]. In secondary HLH, it is important to treat the underlying cause [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral infection, which is often respiratory, is a common cause of secondary HLH and CMV‐associated HLH appear to be a particular risk in patients with ulcerative colitis treated with azathioprine [2]. In secondary HLH, it is important to treat the underlying cause [1].…”
Section: Discussionmentioning
confidence: 99%
“…HLH may be primary (genetic etiology) or secondary to malignancies, autoimmune disease, or infections (most commonly viral). There have been multiple previous reports of cytomegalovirus (CMV) associated HLH developing in patients with ulcerative colitis receiving azathioprine [2]. We report the successful management of this syndrome with ganciclovir, corticosteroids and the new interleukin 1 inhibitor anakinra.…”
Section: Introductionmentioning
confidence: 92%
“…A retrospective study demonstrated that patients with IBD using azathioprine or 6‐mercaptopurine significantly increased the risk of developing EBV‐associated lymphoma 34 . Hemophagocytic syndrome has also been increasing in IBD patients treated with azathioprine and infliximab 35–38 …”
Section: Caebv Enteritis and Ibdmentioning
confidence: 99%
“…Cytomegalovirus-associated hemophagocytic lymphohistiocytosis in inflammatory bowel disease patients has rarely been reported. 2,3 At least 5 cases have occurred specifically in inflammatory bowel disease patients treated with azathioprine. 3 Theoretically, immunosuppression with azathioprine favors cytomegalovirus reactivation, which, in combination with the underlying inflammatory state, may predispose patients to uncontrolled cytokine activation and thus, hemophagocytic lymphohistiocytosis.…”
mentioning
confidence: 99%
“…2,3 At least 5 cases have occurred specifically in inflammatory bowel disease patients treated with azathioprine. 3 Theoretically, immunosuppression with azathioprine favors cytomegalovirus reactivation, which, in combination with the underlying inflammatory state, may predispose patients to uncontrolled cytokine activation and thus, hemophagocytic lymphohistiocytosis. 2 Antiviral therapy in conjunction with corticosteroids, immunoglobulins, and chemotherapy has been used.…”
mentioning
confidence: 99%